The English Pragmatic Competence of Indonesian English Speakers - Ermansyah Malik (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The aim of the research were (1) to examine participants’ pragmatics competence toward English formal, neutral and formal request, (2) to find evidence of the participants’ lack of pragmatics competence toward various setting of English pragmatics situations.qualitative and quantitative methods were applied to analyze the result of the findings. English grammar competence test was given to determine the subjects’ grammar competence. The English pragmatic test was given to determine the subject’ competence on English pragmatic.the subjects of the research were grouped into 3 categories; group a, subjects whose English grammar competence are at basic level, group b, subjects whose English grammar competence are at intermediate level and group c, subjects whose English grammar competence are at advance level. Each group consists of 5 individuals, who have no prior information of the test model and the aims of the research. Ielts model test is administered before the pragmatic competence test, to groups the subjects of the research. There are 3 parts of the English pragmatic competence which researcher applied to determine the result of the research, (1) identifying formal, informal and neutral request utterances, (2) expressing willingness and unwillingness with reasons in using the utterances (3) answering appropriately to multiple questions.the result of the research shows different finding from each of the English grammar competence level. The research result unsurprisingly shows low level of pragmatics competence at intermediate and basic level of grammar competence. Different result showed at higher level whereas the relationship between grammar and pragmatic competence is strong.